1992
DOI: 10.3109/00365519209115511
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive enzyme-linked immunosorbent assay for measurement of autoantibodies to human thyroid peroxidase

Abstract: The development of a sensitive assay for detection of autoantibodies against one of the major thyroid antigens, thyroid peroxidase (TPO), is described. TPO was purified from human thyroid tissue by: (1) isolation of thyroid microsomes using homogenization and differential centrifugation, (2) solubilization of membrane proteins by Zwittergent 3-14, and (3) anion exchange liquid chromatography on a FPLC Mono Q column. Autoantibodies against TPO (TPO-Ab) were measured using an enzyme-linked immunosorbent assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Still, the sensitivity and specificity of the assay of anti‐hTg autoantibodies may have been underestimated, as they were more dependent on the method used than those of anti‐hTPO autoantibodies 12 . Anti‐hTg autoantibodies (≥ 1·0 U/ml) have also been detected in 10·4 ± 0·5% of 13 344 disease‐free subjects in the USA, 13 in agreement with previous estimates 14 . Their prevalence was higher in females and increased with age 13,15 , 16 and following viral infections 17 …”
Section: Prevalence Diagnostic and Prognostic Significancesupporting
confidence: 84%
“…Still, the sensitivity and specificity of the assay of anti‐hTg autoantibodies may have been underestimated, as they were more dependent on the method used than those of anti‐hTPO autoantibodies 12 . Anti‐hTg autoantibodies (≥ 1·0 U/ml) have also been detected in 10·4 ± 0·5% of 13 344 disease‐free subjects in the USA, 13 in agreement with previous estimates 14 . Their prevalence was higher in females and increased with age 13,15 , 16 and following viral infections 17 …”
Section: Prevalence Diagnostic and Prognostic Significancesupporting
confidence: 84%
“…Many studies have shown a higher sensitivity and specificity of enzymelinked immunosorbent assays (ELISA) and RIA compared to assays based on passive haemagglutination in detecting thyroid autoimmunity. This has been found both when the diagnosis has been based on a combination of clinical and biochemical features (Laurberg & Pedersen, 1988;Laurberg et al, 1992) and when histopathological studies have indicated autoimmune thyroiditis with lymphocyte infiltration in the thyroid (Kasagi et al, 1996;Arai et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…TPO antibodies (TPO-Abs) appear to be involved in the tissue destructive processes associated with the hypothyroidism observed in Hashimoto's and atrophic thyroiditis [6]. Evaluation of the diagnostic value of an anti-TPO assay in patients with different types of thyroid disease and in controls showed increased anti-TPO antibodies in >90% patients with active autoimmune thyroiditis [7,8]. Measurement of this autoantibody is useful for settling the diagnostic quandary demonstrated by the evident inconsistency between thyroid function test parameters.…”
mentioning
confidence: 99%